Effects of porcine somatotropin dosage and lysine level on growth performance of growing pigs - Fitzner, G.E.; Weeden, T.L.; Schricker, B.R.; Hines, Robert H.; Nelssen, Jim L.; Goodband, Robert D.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty crossbred barrows initially weighing 70.5 lb were used in a 5 wk trial to determine the optimum dosage of porcine somatotropin (PST) required to promote maximum growth response in growing pigs fed diets containing either 1.0 or 2.0% lysine. Pigs received a daily injection of placebo or 2, 4, or 8 mg pST in combination with one of two experimental diets containing either 1.0 or 2.0% dietary lysine. Increasing the dosage of pST of pigs fed both diets resulted in an increase in average daily gain (ADG), a reduction in average daily feed intake (ADFI), and an improvement in feed conversion (F/G). Average backfat, calculated from ultrasonic measurements at the first rib, last rib, and last lumbar vertebra, was reduced in pigs fed both diets as pST dosage increased. Serum pST increased and urea nitrogen decreased for pigs fed both diets as pST dosage increased. The improvement in ADG and F/G of pigs fed both diets was quadratic, indicating that a plateau was achieved between 4 and 8 mg/d pST administration. The serum urea nitrogen response appeared to plateau near 8 mg/d. The combination of these response criteria indicates that the dosage required for maximum response is about 7 mg/d pST, whereas the more optimum level of pST administration may be about 5 mg/d for growing pigs fed diets containing 1.0 or 2.0% lysine.
Keywords: Swine; GF; Repartition; Performance; Lysine